Process Mapping Based on Memory Access Traces - Cruz, Eduardo H. M.; Alves, Marco A. Z.; Navaux, Philippe O. A. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2010)
Process mapping is a technique widely used in parallel machines to provide performance gains by improving the use of resources such as interconnections and cache memory hierarchy. The problem to find the best mapping is considered NP-Hard and, in shared memory environments, there is the additional difficulty to find the communication pattern, which is implicit and occurs through memory accesses. In this context, this work aims to improve the performance of parallel applications that use shared memory. For that, it was developed a method for analysis of the shared memory which identifies the mapping without requiring any previous knowledge of the application behavior. Applications from the NAS Parallel Benchmarks (NPB) were used in these experiments, showing performance gains of up to 42% compared to the native scheduler of the operating system.